Analysis Determinant Factors Effect on Migrant Workers’ Remittances Flow to the CLMV Countries - Hor, Chantha; Pheang, Pheara (International Journal of Economics and Financial Issues, 2017)
This paper aims to investigate the determinant macroeconomic variables and non-economic factors influencing the migrant workers’ remittances flow to the CLMV countries (Cambodia, Laos, Myanmar, and Vietnam). This study employs fixed-effect and random-effect models to analyze the panel data set over the periods of 16 years (2000-2015). The results show that the GDP per capita of origin country, the official exchange rate of the home country, and political stability index of home country are significant negative effects on remittances inflow to the CLMV countries. Higher number of migrants to the home country’s population increase the remittances inflow to the home countries. Majors of most host country’s GDP per capita (Japan, South Korea, and Singapore) are positive effects on the remittances, except for the Thai’s GDP per capita. All dummy variables show expected results. Keywords: CLMV, Macroeconomics, Remittances JEL Classification: E01, E31, N15, N35, C22, O53, F22, F24